Jane Austen among Women - Kaplan, Deborah, 1950-; Project Muse.; Project Muse. (1992)
In an age when genteel women wrote little more than personal letters, how did Jane Austen manage to become a novelist? Was she an isolated genius who rose to fame through sheer talent? Did she draw strength from the support of her family, or from woman writers who went before her? In Jane Austen among Women Deborah Kaplan argues that these explanations are either misleading or insufficient. Austen, Kaplan contends, participated actively in a women's culture that promoted female authority and achievement--a culture that not only helped her become a novelist but also influenced her fiction. Kaplan shows that women of Jane Austen's family and community endorsed their society's male-dominated culture and its "domestic ideology" while also in their intimate friendships with other women-expressing distance from it. Drawing on this framework of women's dual perspectives, Kaplan offers new insights about Austen's life and work, including her decision not to marry and her attempts to keep her writing secret. She also examines Austen's fictional representations of loyalties divided between the dominant patriarchal values of her community and the unconventional, even subversive, values and expressions that circulated privately among women. Jane Austen among Women presents a fresh, interdisciplinary approach to feminist literary studies. The discussion of Austen and her family and community is based on extensive research in letters, diaries, poems, and memoirs. Much of this material, discovered by the author in British record offices and in private hands, has never before been published. Kaplan also provides new readings of Austen's fiction, including detailed discussions of the often-ignored juvenilia and the transitional producations Lady Susan and The Watsons. A perceptive and original account of the author in her social among Women will English society, and the relation of gender and literature.
Divided Loyalties -- Genteel Domesticity -- Compliant Women -- The Women's Culture -- Portraits of the Woman Writer -- Circles of Support -- Assuming Spinsterhood -- Representing Two Cultures -- The Juvenilia: Convenient Ambiguities -- The "Middle" Fictions: Visible Conflicts -- Pride and Prejudice: Cultural Duality and Feminist Literary Criticism.
Includes bibliographical references (pages 207-237) and index.
Description based on print version record.
Keywords: Austen, Jane; Austen, Jane, -- (1775-1817) -- Critique et interpretation; Austen, Jane -- 1775-1817; Austen, Jane, -- 1775-1817.; Austen, Jane, -- 1775-1817.; Austen, Jane, -- 1775-1817.; Frau; Femmes et litterature -- Grande-Bretagne -- 19e siecle; Frau; Feminismus; Women and literature; Novelists, English; Women and literature -- England -- History -- 19th century; Novelists, English -- 19th century -- Biography; England; 1800-1899; English fiction; Electronic books; Biographies; History; Biography; Electronic books